If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4z + -1u)(7z + 7u) = 0 Reorder the terms: (-1u + 4z)(7z + 7u) = 0 Reorder the terms: (-1u + 4z)(7u + 7z) = 0 Multiply (-1u + 4z) * (7u + 7z) (-1u * (7u + 7z) + 4z * (7u + 7z)) = 0 ((7u * -1u + 7z * -1u) + 4z * (7u + 7z)) = 0 Reorder the terms: ((-7uz + -7u2) + 4z * (7u + 7z)) = 0 ((-7uz + -7u2) + 4z * (7u + 7z)) = 0 (-7uz + -7u2 + (7u * 4z + 7z * 4z)) = 0 (-7uz + -7u2 + (28uz + 28z2)) = 0 Reorder the terms: (-7uz + 28uz + -7u2 + 28z2) = 0 Combine like terms: -7uz + 28uz = 21uz (21uz + -7u2 + 28z2) = 0 Solving 21uz + -7u2 + 28z2 = 0 Solving for variable 'u'. Factor out the Greatest Common Factor (GCF), '7'. 7(3uz + -1u2 + 4z2) = 0 Factor a trinomial. 7((-1u + -1z)(u + -4z)) = 0 Ignore the factor 7.Subproblem 1
Set the factor '(-1u + -1z)' equal to zero and attempt to solve: Simplifying -1u + -1z = 0 Solving -1u + -1z = 0 Move all terms containing u to the left, all other terms to the right. Add 'z' to each side of the equation. -1u + -1z + z = 0 + z Combine like terms: -1z + z = 0 -1u + 0 = 0 + z -1u = 0 + z Remove the zero: -1u = z Divide each side by '-1'. u = -1z Simplifying u = -1zSubproblem 2
Set the factor '(u + -4z)' equal to zero and attempt to solve: Simplifying u + -4z = 0 Solving u + -4z = 0 Move all terms containing u to the left, all other terms to the right. Add '4z' to each side of the equation. u + -4z + 4z = 0 + 4z Combine like terms: -4z + 4z = 0 u + 0 = 0 + 4z u = 0 + 4z Remove the zero: u = 4z Simplifying u = 4zSolution
u = {-1z, 4z}
| 180-67= | | 0+(-21)=b | | 8*AB=-4AB | | 0.15x-3=0.3(x-8) | | 3/4g÷2.5=4/3g-2.4 | | 20x^6+16x^4-5x^2-4=0 | | 5t-13=12-13 | | xsquared+4x-32=0 | | 15+4t-t^2=0 | | 3m^2-6mn+5m-10n=0 | | 7h/2=8/9 | | H=5/6(a-9) | | 175=(78)(0.03)(x) | | 8x+7=143 | | 9/11x=3/8 | | sen^2x-cos^2x/cosx*senx=0 | | 5x-4+3x+10=x | | 13/8y-14=-1 | | x^2+5-20=0 | | 6y+-3x=15 | | -7+8=k | | -7-17=-143 | | 16/u=4 | | 35p-56=28-7p | | 2m=4.8 | | x/100=5/9 | | Tan15=6/x | | 1/3=1/12d | | 19(3w+5r)= | | 9(6a+7)-6-3a= | | 45/100=x/39 | | 3/5*12.6 |